Implementasi SAK EMKM Dalam Penyusunan Laporan Keuangan - Muhammad Fadhil Ar'razi; Khozin Arief; Sudjana Sudjana (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
Pisang Mesir Indonesia is one of the micro, small and medium enterprises (MSMEs) which is engaged in the production and sale of packaged snacks, namely banana chips. This company has made financial records but the method used is still cash-based so it does not reflect the actual financial situation and is not in accordance with SAK EMKM. This is due to the limited knowledge of owners and employees regarding the preparation of correct financial statements and not yet aware of the existence of SAK EMKM. This study aims to assist Pisang Mesir Indonesia in compiling financial reports based on SAK EMKM. The research method used in this research is descriptive qualitative. Data collection was carried out by means of observation, interviews, and documentation.